Present dynamics of the Guadiana estuary - Garel, Erwan (2020)
Estuaries offer natural protection from energetic ocean waves, and have been used as natural harbour and inland waterways since the beginning of civilisation. Nowadays, most of the largest cities in the world are located on estuaries that must cope with increasing economic and industrial developments. These sheltered coastal areas are also one of the most productive types of ecosystems on Earth and are of considerable value for humans and wildlife. Understanding the dynamics of estuaries is fundamental to maintain a balance between exploitation and conservation. In particular, the assessment of various features of uttermost socio-ecological importance (such as water quality, flood risk, ecosystem health and morphodynamics) must rely on a thorough knowledge of the operating hydrodynamic and sediment transport processes.